Mechanical response of fine laterite-modified polyester matrix composites. (23rd February 2017) - Pai, Anand; Padmaraj, N.H.; Chethan, K.N.; Vibhor, Saini
Abstract : The current work is aimed at evaluating the feasibility of laterite as a novel inorganic constituent for polyester matrix composites. Three compositions of the laterite reinforced polyester composites have been synthesised by the hand lay-up technique for varying weight fraction (10–40 wt.%) of laterite particulates of size ~75 μm). The microstructures of the composites were examined through optical microscopy. The effect of laterite addition to polyester on the mechanical properties: density, hardness, tensile strength and impact strength were systematically investigated. The addition of laterite imparted a dark maroon colouration to the composites. The results show that on increasing content of laterite, there was an increase in tensile modulus, tensile elongation, hardness and impact strength while the ultimate tensile strength and the brittleness were found to decrease. The density and porosity of the composites were found to increase with higher laterite content which could be addressed with finer particulate size of laterite. Laterite being a natural soil boosts the refractory and inflammability characteristics of polyester composites. Hence, the deployment of laterite in polymer matrices as micro-fillers is quite encouraging.